2016
DOI: 10.11648/j.ajam.20160403.16
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Variability and Linear Trend Models on North-West Part of Bangladesh for the Last 40 Years

Abstract: Rainfall has been extensively considered as one of the initial point towards the apprehension of climate change courses. Bangladesh is recently experiencing climate change impact related to hazards like cyclone, rainfall, flood, draught etc. Climate variable like rainfall is the most important parameter which is linked with agricultural aspects too for this country. Most of the rain occurred during monsoon period in Bangladesh. This study investigates temporal variability of rainfall and liner trend models on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…A decreasing trend of monsoon rainfall has been observed in the northwestern region. Other studies have indicated a similar trend for most stations, especially in the northwestern hydrological zone of Bangladesh (M. Ahasan et al, 2010;Bari et al, 2016; A. M. Rahman, 2016). The tropical monsoon depression plays a major role in producing a huge amount of rain during the summer monsoon in Bangladesh.…”
Section: Past Trend Of the Annual Total Rainfall And Monsoon Rainfallsupporting
confidence: 57%
See 1 more Smart Citation
“…A decreasing trend of monsoon rainfall has been observed in the northwestern region. Other studies have indicated a similar trend for most stations, especially in the northwestern hydrological zone of Bangladesh (M. Ahasan et al, 2010;Bari et al, 2016; A. M. Rahman, 2016). The tropical monsoon depression plays a major role in producing a huge amount of rain during the summer monsoon in Bangladesh.…”
Section: Past Trend Of the Annual Total Rainfall And Monsoon Rainfallsupporting
confidence: 57%
“…In contrast, the eastern and northeastern regions are characterized by high temperatures, low humidity, and minor seasonal uctuations in rainfall (Acharjee & Shariot-Ullah, 2021; Salem et al, 2017). Past evidence in the northwestern region reveals that unpredictable rainfall-induced droughts and oods threaten agriculture, ecosystems, and the broader economy (Ahasan et al, 2010;Mohsenipour et al, 2020;Rahman, 2016;Shahid & Behrawan, 2008;Alam et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…From supplementary (Table S3) the t test statistic indicated that the monsoon and the winter rainfall trend in the northwestern region was significant at the 5 % level. Rahman and Kamal (2016) analyzed rainfall variability and linear trend models on northwestern part, Bangladesh. They analyzed data of the 40 years over the northwestern part of Bangladesh using a linear trend model.…”
Section: Temporal Trend Analysis Of Annual and Seasonal Rainfallmentioning
confidence: 99%
“…The annual precipitation is 2,030 mm. The dry season generally ranges from December to February, and the rainy season lasts from June to September (Rahman et al 2016b). The new town project was established to reduce the overpopulation in the capital city of Dhaka, the population density of which was 57,167/km 2 in 2011 (Khatun et al 2015).…”
Section: Study Areamentioning
confidence: 99%